The Holy Sail - Al-Mahmoud, Abdulaziz; Translated by Karim Traboulsi (Doha Hamad Bin Khalifa Univ. Press, 2015)
Oblivious to the invasions, massacres and religious fanaticism that characterise the 15th century, a young girl falls in love with a noble Arabian tribal leader. But all eyes are on the Portuguese fleets in the Arabian Gulf, intent on securing the profitable spice trade. Abdulaziz Al-Mahmoud weaves a tapestry of momentous historical events with stories of love, honour and nobility, while guiding us around the medieval world of Lisbon, Cairo, Jeddah and Istanbul. The Holy Sail brings to life a neglected episode of history that impacted not only the region but the world for centuries to come.
Include Map, Glossary and Bibliography
Keywords: Spice trade -- Arabian Peninsula -- Portuguese fiction